From Equation 1
![(x)/(2) + (2y)/(3) = - 1](https://img.qammunity.org/2023/formulas/mathematics/high-school/phgyq4iohm4risglidozyad7w5llvay7jt.png)
![(3x + 4y)/(6) = - 1](https://img.qammunity.org/2023/formulas/mathematics/high-school/3cvp9y2qnembrwimouql7b6lhkj08uq6kt.png)
![3x + 4y = - 6](https://img.qammunity.org/2023/formulas/mathematics/high-school/ofqnqbb0f9dufyrnwyftruzy61svx2l6t2.png)
From Equation 2
![x - (y)/(3) = 3](https://img.qammunity.org/2023/formulas/mathematics/high-school/nmvcnny35opkr1aoa9j8kkkdszpvn0pucn.png)
![(3x - y)/(3) = 3](https://img.qammunity.org/2023/formulas/mathematics/high-school/9ylegft5kecnbin3q03ux6dbno47dlmf3o.png)
![3x - y = 9](https://img.qammunity.org/2023/formulas/mathematics/high-school/c1dwg9c73e8svp1vmvhapd9c23mmxh19ho.png)
By eliminating ;;
For that multiply equation 2 by 4
12x - 4y = 36 _(3)
By taking equation (1) and (3)
3x + 4y = -6
12x - 4y = 36
__________
15x = 30
x = 30/15
x = 2
Putting the value of x in 2
![3(2) - y = 9](https://img.qammunity.org/2023/formulas/mathematics/high-school/c71i9e7avcxcj5perm64whj0ysaa7mv70u.png)
![6 - y = 9](https://img.qammunity.org/2023/formulas/mathematics/high-school/lsfcvgugd7xg4rh44s3hc9kd0774qx7lec.png)
![6 - 9 = y](https://img.qammunity.org/2023/formulas/mathematics/high-school/2z56h2d98iyzikz53h6kda3e28l2a4os76.png)
![-3 = y](https://img.qammunity.org/2023/formulas/mathematics/high-school/qvqflew6pp12d99ge2xwg29qb962q6vcd4.png)
So The value of x = 2 and y = -3